Applying citizens’ juries as a driver of the sustainability transformation in the global south: An introduction to the method - Nilgen, Marco; Vollan, Björn (CGIAR Initiative on Low-Emissions Food Systems, 2023)
While the last blog post provided a brief introduction to the citizens’ jury (CJ) method and its potential in the Global South, today’s post takes you further along our planned research proceedings within the context of the CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+). More specifically, it will go into more detail on the research questions we aim to tackle and the methodology we intend to use in doing so. We know from previous research that CJs can counter elite capture and decision-making biases, thereby potentially enhancing public policy processes and their outcomes. At the same time, CJs’ policy recommendations tend to gain acceptance among both community members and decision-makers in different cultural contexts making them valuable in addressing power imbalances and increasing community agency in complex socioecological policy environments. Our research aims to advance the theoretical and empirical understanding of CJs in the Global South, exploring their potential as “deep leverage points” that can bring about transformative change to complex socioecological systems (e.g., multilayered food systems). We argue that CJs can influence norms, values, and paradigms, ultimately enhancing the legitimacy of decision-making processes.